Systematic review: Incidence, risk factors, survival and treatment of bone metastases from colorectal cancer - Troels Dreier Christensen; Sandra Galinska Jensen; Finn Ole Larsen; Dorte Lisbet Nielsen (Journal of Bone Oncology, 2018)
Background: Bones are not considered a frequent metastatic site in patients with colorectal cancer (CRC). The purpose of the present study was to determine the incidence of bone metastases (BM) in CRC, to identify possible risk factors for BM, survival after BM, and effect of treatment of BM including antiresorptive treatment. Material and methods: A computer-based literature search was carried out using PubMed and EMBASE. Results: We included 29 studies. One randomized placebo controlled trial (RCT) study, two autopsy studies, five register studies, and twenty retrospective cohort studies. The studies described different cohorts making direct comparison difficult. Three studies analysed the effect of different treatments for BM including one RCT study. Conclusion: The incidence of bone metastases was 3–7% in patients with CRC, and it was not possible to detect an increase in incidence over time. The most well established risk factors for BM are rectal cancer, having lymph node invasion at surgery of primary tumor, and lung metastases at any time. Other risk factors such as RAS mutation status have been suggested but results are not conclusive. Survival ranges from 5 to 21 months after diagnosis of BM depending on cohort, with survival of about 8 months in unselected patients. Several variables have been suggested as potential prognostic markers but are all poorly investigated. Treatment of BM is not well investigated, though patients seem to benefit from bisphosphonate treatment with regard to lower risk of skeletal related events. This review highlights the need for new research in the area. Keywords: Colorectal cancer, Bone metastases, Incidence, Risk factors, Survival, Bisphosphonate treatment